The influence of duration of confinement towards morphine dependence intensity in conditioned place preference (CPP) model - Abdul Basir, Siti Najihah; Suhaimi, Maryam Saadah; Syd Mohmad Faudzi, Syed Mohd Syahmi; Ridzwan, Irna Elina (2015)
Introduction: Conditioned Place Preference (CPP) continues to be one of the most popular models to study the dependence effects of substance abuse. This study is divided into three main phases which are pre-conditioning, conditioning and post-conditioning phases. It can be conducted using different protocols which can be used to investigate the effects of drug dependence. Since there is not much study done to investigate the effects of duration of confinement, this study is conducted to figure out the effects of different duration of confinement towards intensity of morphine dependence.